Investigation of the Interaction Mechanism of Solid Particles under Shock Waves - Xu Peng; Shunyao Wang; Guoning Rao; Bin Li; Wanghua Chen (Shock and Vibration)
To deeply understand the interaction mechanism between the two phases, both shock wave experiments and computational fluid dynamics (CFD) simulations are carried out to study the propagation of shock waves and the dispersion process of solid quartz sand particles. The results show that transmission and reflection occur during the interaction between the shock wave and particle. When the Mach number is 1.53, the incident pressure is 154.6 kPa and the reflected pressure is 342.4 kPa. The transmitted pressure rapidly decays due to the exchange of momentum and energy, the particle front gradually changes from horizontal to mushroom shape, and a rising three-dimensional annular vortex is formed obliquely above the particles due to the entrainment effect. The simulated and experimental results are in good agreement, thereby indicating the validity of the numerical model. In addition, based on the response surface method and a series of experimental data, a mathematical model of the dispersion distance of solid particles under the action of shock waves is proposed. It is beneficial for prediction and scientific research for the development of industrial systems.